PENGARUH FINANCIAL LEVERAGE TERHADAP RETURN ON EQUITY DAN EARNING PER SHARE PADA PERUSAHAAN SEKTOR TELEKOMUNIKASI YANG LISTED DI BURSA EFEK INDONESIA - Jouhar Fayahaqi; Sumani Sumani; Lilik Farida (BISMA: Jurnal Bisnis dan Manajemen, 2015)
Abstract:The purposes of this research are to analyze: (a) the effect of financial leverage that measured as debt to assets, long-term debt to equity, and debt to equity on earnings (Return on Equity); (b) the effect of financial leverage that proxied by debt to assets, long-term debt to equity, and debt to equity on earnings (Earning per Share or EPS); and (c) the dominant effect of financial leverage on ROE and EPS in the telecommunications sector companies listed in the Indonesia Stock Exchange. This research examines 5 companies. Multiple linear regression analysis was used to test the hypothesis.Results show that financial leverage affects profitability (both ROE and EPS). Results also show that debt to assets ratio is the dominant variable affecting ROE and EPS. Keywords: Financial Leverage, ROE, and EPS